Inclusive quarkonium production at forward rapidity in pp collisions at √s=8 TeV - Adam, Jaroslav; Angelov, Venelin; Bock, Friederike; Busch, Oliver; Deisting, Alexander; Fleck, Martin; Glässel, Peter; Karayan, Lilit; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; et al. (The European physical journal. C, Particles and fields, 2016)
We report on the inclusive production cross sections of $${\mathrm{J}/\psi }$$J/ψ, $${\psi (\mathrm{2S})}$$ψ(2S), $$\mathrm{\Upsilon }$$Υ(1S), $$\mathrm{\Upsilon }$$Υ(2S) and $$\mathrm{\Upsilon }$$Υ(3S), measured at forward rapidity with the ALICE detector in $$\mathrm{pp}$$ppcollisions at a center-of-mass energy $$\sqrt{s}=8$$s=8 TeV. The analysis is based on data collected at the LHC and corresponds to an integrated luminosity of 1.23 pb$$^{-1}$$-1. Quarkonia are reconstructed in the dimuon-decay channel. The differential production cross sections are measured as a function of the transverse momentum $${p_\mathrm{T}}$$pTand rapidity y, over the $${p_\mathrm{T}}$$pTranges $$0<{p_\mathrm{T}}<20$$0<pT<20 GeV/c for $${\mathrm{J}/\psi }$$J/ψ, $$0<{p_\mathrm{T}}<12$$0<pT<12 GeV/c for all other resonances, and for $$2.5<y<4$$2.5<y<4. The cross sections, integrated over $${p_\mathrm{T}}$$pTand y, and assuming unpolarized quarkonia, are $$\sigma _{{\mathrm{J}/\psi }} = 8.98\pm 0.04\pm 0.82$$σJ/ψ=8.98±0.04±0.82 $$\upmu $$μb, $$\sigma _{{\psi (\mathrm{2S})}} = 1.23\pm 0.08\pm 0.22$$σψ(2S)=1.23±0.08±0.22 $$\upmu $$μb, $$\sigma _{\mathrm{\Upsilon }\mathrm{(1S)}} = 71\pm 6\pm 7$$σΥ(1S)=71±6±7 nb, $$\sigma _{\mathrm{\Upsilon }\mathrm{(2S)}} = 26\pm 5\pm 4$$σΥ(2S)=26±5±4 nb and $$\sigma _{\mathrm{\Upsilon }\mathrm{(3S)}} = 9\pm 4\pm 1$$σΥ(3S)=9±4±1 nb, where the first uncertainty is statistical and the second one is systematic. These values agree, within at most $$1.4\sigma $$1.4σ, with measurements performed by the LHCb collaboration in the same rapidity range.
Im Titel steht "s" unter dem Wurzelsymbol
ALICE collaboration: J. Adam, V. Anguelov, F. Bock, O. Busch, A. Deisting, M.G. Fleck, P. Glässel, L. Karayan, S. Klewin, M.L. Knichel, L. Leardini, J. Mercado Pérez, H. Oeschler, K. Oyama, Y. Pachmayer, F. Reidt, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, M.A. Völkl, D.F.Weiser, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und 957 weitere]
Gesehen am 04.08.2020